2005
DOI: 10.1074/jbc.m503273200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-limited Oat

Abstract: We recently reported that cultivation of oat (Avena sativa L.) without phosphate resulted in plasma membrane phosphoglycerolipids being replaced to a large extent by digalactosyldiacylglycerol (DGDG) (Andersson, M. X., Stridh, M. H., Larsson, K. E., Liljenberg, C., and Sandelius, A. S. (2003) FEBS Lett. 537, 128 -132). We report here that DGDG is not the only non-phosphorouscontaining lipid that replaces phospholipids but that also the content of glucosylceramides and sterolglycosides increased in plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…6). In agreement with this hypothesis, it has been recently demonstrated that DGDG accumulation is highly up-regulated by Pi starvation in the plasma membrane fraction of oat roots and that PLD-type and PAP activity are the major lipase activities induced by Pi starvation in nonplastidic root membranes (20,27).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…6). In agreement with this hypothesis, it has been recently demonstrated that DGDG accumulation is highly up-regulated by Pi starvation in the plasma membrane fraction of oat roots and that PLD-type and PAP activity are the major lipase activities induced by Pi starvation in nonplastidic root membranes (20,27).…”
Section: Discussionsupporting
confidence: 51%
“…Although the participation and induction of genes involved in SQDG (SQD1 and SQD2), DGDG (DGD1 and DGD2), and MGDG (MGD2 and MGD3) biosynthesis in both roots and leaves as a response to Pi starvation have been experimentally demonstrated (12,13), no direct evidence has been reported to our knowledge on the existence of specific phospholipases that hydrolyze phospholipids to provide DAG for the synthesis of nonphosphorus lipids. Two potential pathways for the hydrolysis of phospholipids to release Pi from its storage source and to produce DAG, the substrate for galactolipid synthesis, have been proposed: a direct pathway involving phospholipase C and an indirect pathway involving PLD and PAP activities (14,19,20). Microarray analysis showed that two genes encoding phospholipases are strongly induced during Pi deprivation in Arabidopsis: NPC4, a member of the PLC family, and PLDZ2.…”
Section: Discussionmentioning
confidence: 99%
“…Envelope membranes were isolated from chloroplasts isolated from 9-to 10-day-old pea seedlings as described (19). Analyses of membrane components and marker enzyme activities were assayed as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…A stable amount of DGDG may be essential for structural and functional stabilization of the chloroplast and thus cell survival. As DGDG can be exported from the chloroplast to replace phospholipids in extraplastidial membranes under P-limited conditions (Sandelius et al, 2003;Andersson et al, 2005;Jouhet et al, 2007), we can't rule out that trafficking of DGDG from the chloroplast to other subcelluar organelles may occur under N-deprivation conditions, especially when the extraplastidic bilayerglycerolipids (e.g., PC and DGTS) are drastically decreased.…”
Section: Remodeling Of the Membrane Glycerolipids In Response To Chanmentioning
confidence: 99%